(untitled) (Journal of the Bangladesh Society of Anaesthesiologists, 2009)
Pain, nausea, vomiting, oedema and poor oral intake are the most common morbidities after general anesthesia and surgery like tonsillectomy. This study was done to evaluate the effectiveness of intravenous dexamethasone (0.15mg/kg) at induction of anaesthesia on post tonsillectomy morbidities. In this prospective randomized double blind study, sixty children of age between 8-12 years, ASA I & II undergoing tonsillectomy under general anaesthesia were randomly assigned into two equal groups of 30 each. They received dexamethasone IV or saline (control) following induction of anaesthesia. Both anesthetic and surgical techniques were standardized. Post operative pain was assessed by visual analogue scale (VAS). Inj. Tramadol 1mg/kg in first 6 hrs and oral paracetamol 10mg/kg in next 24 hrs were administered as rescue analgesic. Incidence of nausea, vomiting, time and quantity of first oral intake were also noted. Patients receiving dexamethasone experienced significantly less pain, nausea and vomiting than control group throughout 24 hrs. Lesser patients required rescue analgesics (23.33% vs. 46.67%) in first 6 hrs. So, it is found that, single intravenous dose of dexamethasone (0.15mg/kg) provided significant analgesia, reduced nausea, vomiting and improved quality of oral intake in paediatric patients who underwent tonsillectomy. Journal of BSA, Vol. 20, No. 1, January 2007 p.13-17